Diversité ethnique et religieuse au collège : entre laïcité souple et rigide - Jean-François Bruneaud (Recherches en Éducation)
This article examines part of the results of a survey on ethnic, cultural and religious diversity in schools. Based on a panel of middle school students from Bordeaux’s regional education authority, the article questions the nature of the schoolchildren’s relationship to French laicity depending on their ethnic origin, religious beliefs and to their affiliations.